Constructing Parentless Childhood in the Animated Film Jumbo (2025): A Critical Discourse Analysis - Andini Dwi Rahmawati; Syafrida Nurrachmi Febrianti (Jurnal Spektrum Komunikasi, 2026)
This study examines how the animated film Jumbo (2025), directed by Ryan Adriandhy, constructs the discourse of parentless childhood through Norman Fairclough’s Critical Discourse Analysis (CDA). Parentless childhood refers to conditions in which children grow without parental presence due to death, separation, or socio economic circumstances. In Indonesia, this phenomenon is a sociocultural issue closely tied to poverty, migration, and shifting family structures. As a mass mediated text, film has the power to shape public perception about social realities through narrative, characters, and visual symbolic elements. Using Fairclough’s three dimensional CDA framework (textual analysis, discourse practice, sociocultural practice), this research analyzes how Jumbo portrays children who live without parents through five main characters: Don, Atta, Mae, and Nurman. Textual findings show that visual cues, dialogue patterns, and character interactions emphasize emotional vulnerability, social exclusion, and the search for belonging. At the discourse practice level, production and audience responses show that the film was intentionally crafted as a social commentary on Indonesia’s increasing issues of bullying, fatherlessness, and broken home dynamics. Meanwhile, sociocultural analysis reveals that the film resonates with real world data on orphanhood, economic hardship, and shifting family norms in contemporary Indonesia. This study contributes to communication studies by showing how animated films function as cultural texts that construct and circulate discourses about childhood and family beyond traditional structures.